Bathimetri di perairan pantai depan Sungai Bahu, Kecamatan Malalayang, Manado - Wandasari Hamid; Frangky E. Kaparang; Heffry V. Dien (Universitas Sam Ratulangi, 2015)
ABSTRACT The word bathymetry come from the Greek. Bathy is depth and metry is the science of measurement. So bathymetry can be defined as the science of measuring and mapping the bottom of waters. It is necessary to have accurate data about the physical state of the waters like shape of the coastline, tidal height and the shape of seabed. So that the objectives of this study are: to map the shape of the coastline, the state of tides and to describe the contours of the seabed. Collecting data using a water depth transect pattern normal to coastline. Tidal height measured using a tide pole. Results showed that the length of the surveyed coastline was 1,327 meters stretching from position 1027'39.9